Modulators of the urokinase-type plasminogen activation system for cancer - Hildenbrand, Ralf; Allgayer, Heike; Marx, Alexander; Ströbel, Philipp (Expert opinion on investigational drugs, 2010)
Importance of the field: The serine protease urokinase-type plasminogen activator (uPA) and its receptor uPAR as well as two specific inhibitors, the plasminogen activator inhibitor type-1 (PAI-1) and type-2 (PAI-2), are involved in the control of extracellular matrix turnover and tumor growth. Data accumulating over the past 20 years have made increasingly clear that the uPA system has a multifunctional role in neoplastic evolution, affecting cancer cell proliferation, tumor angiogenesis, adhesion and migration.Areas covered in this review: Several therapeutic strategies inhibiting the uPA system have been or are currently being developed for suppression of tumor growth. This review examines the role of the uPA system in tumor progression and assesses the various therapeutic strategies developed to selectively exploit this system.What will the reader gain: We focus on the therapeutic developments of the last 15 years. In addition to antibodies and recombinant uPA- or uPAR-derived proteins, various antagonistic peptides as well as small molecules have been designed and synthesized that inhibit the uPA system, leading to reduced tumor progression.Take home message: The multifunctional potential of the uPA system in cancer has rendered this system an attractive novel target for anticancer therapy. A few novel tumor biology-based therapeutic strategies reported here, opening new ways for patient-optimized and individualized cancer therapy. It may be the right time to evaluate the hypothesis that the uPA system plays a pivotal role in cancer progression and that targeting this system will lead to clinical benefit in cancer patients.
Gesehen am 15.05.2023